Postoperative Morbidity by Procedure and Patient Factors Influencing Major Complications Within 30 Days Following Shoulder Surgery. Issue 10 (9th October 2014) - Shields, Edward; Iannuzzi, James C.; Thorsness, Robert; Noyes, Katia; Voloshin, Ilya
Background: Little data are available to prioritize quality improvement initiatives in shoulder surgery. Purpose: To stratify the risk for 30-day postoperative morbidity in commonly performed surgical procedures about the shoulder completed in a hospital setting and to determine patient factors associated with major complications. Study Design: Cohort study; Level of evidence, 3. Methods: This retrospective study utilized the National Surgical Quality Improvement Program (NSQIP) database from the years 2005 to 2010. Using Current Procedural Terminology codes, the database was queried for shoulder cases that were divided into 7 groups: arthroscopy without repair; arthroscopy with repair; arthroplasty; clavicle/acromioclavicular joint (AC) open reduction and internal fixation (ORIF)/repair; ORIF of proximal humeral fracture; open tendon release/repair; and open shoulder stabilization. The primary end point was any major complication, with secondary end points of incisional infection, return to the operating room, and venothromboembolism (VTE), all within 30 days of surgery. Results: Overall, 11, 086 cases were analyzed. The overall major complication rate was 2.1% (n = 234). Factors associated with major complications on multivariate analysis included: procedure performed ( P < .001), emergency case ( P < .001), pulmonary comorbidity ( P < .001), preoperative blood transfusion ( P = .033), transfer from an outside institution ( P = .03), American Society of Anesthesiologists (ASA) score ( P = .006), wound class ( P < .001), dependent functional status ( P = .027), and age older than 60 years ( P = .01). After risk adjustment, open shoulder stabilization was associated with the greatest risk of major complications relative to arthroscopy without repair (odds ratio [OR], 5.56; P = .001), followed by ORIF of proximal humerus fracture (OR, 4.90; P < .001) and arthroplasty (OR, 4.40; P < .001). These 3 groups generated over 60% of all major complications. Open shoulder stabilization had the highest odds of reoperation (OR, 8.34; P < .001), while ORIF of proximal humerus fracture had the highest risk for VTE (OR, 6.47; P = .001) compared with the reference group of arthroscopy without repair. Conclusion: Multivariable analysis of the NSQIP database suggests that open shoulder stabilization, ORIF for proximal humerus fractures, and shoulder arthroplasty are associated with the highest risk of major complications within 30 days after shoulder surgery in a hospital setting. Age, functional status, ASA score, pulmonary comorbidity, emergency case, preoperative blood transfusion, and transfer from an outside institution are patient variables that significantly influence complication risk.